Relationships matter! Social safeness and self‐disclosure may influence the relationship between perceived social support and well‐being for in‐person and online relationships. Issue 12 (16th August 2022) - Nguyen, Lina; Phillips, Cara V.; Rodriguez, Amelia; Young, Amber R.; Ramdass, Jeff V.
Abstract: We investigated the relationship between perceived social support and mental well‐being in in‐person and online contexts using relational regulation theory as a guiding theoretical framework. Prior research consistently finds a positive link between perceived social support and better well‐being. In our study, we investigated the relationship between perceived social support and mental well‐being in in‐person and online contexts using relational regulation theory as a guiding theoretical framework. More specifically, the present research investigates whether perceived social support and better mental well‐being are associated with increased self‐disclosure or social safeness, and whether the relationships are similar for in‐person and online contexts. Participants (Study 1: N  = 268 MTurk Users; Study 2: N  = 216 MTurk Users) completed measures of perceived social support, self‐disclosure, social safeness, and mental well‐being. In both correlational studies, perceived social support was positively related to well‐being. Both self‐disclosure and social safeness mediated the relationship between perceived social support and well‐being for in‐person relationships. For online relationships, a person may only need to feel socially safe to have better mental well‐being. Future research should employ experimental manipulations to expand upon these findings.